1995
DOI: 10.1177/152660289500200207
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results with the Palmaz Stent in the Superficial Femoral Artery

Abstract: Purpose: Femoral stenting has demonstrated inconsistent and often disappointing long-term results. To compare our experience, we retrospectively analyzed a series of patients who had Palmaz balloon-expandable stents placed exclusively for superficial femoral artery (SFA) lesions. Methods: From January 1990 to November 1993, 39 patients were evaluated for claudication (79%) or critical ischemia in 42 limbs. The culprit lesions were confined to the SFA: 24 (57%) occlusions and 18 (43%) stenoses, including 3 rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…11,12 For example, a 7% rate of grade ՆC dissection with cryoplasty 12 and dissection rates ranging from 1% to 60% with percutaneous angioplasty 13 have been previously described. The low (0.1%) TALON 30-day occlusion and thrombosis rate also compared well with the data previously reported for stents (as high as 4.8% 14 ). Embolism was observed in 0.1% of the lesions treated.…”
Section: Discussionsupporting
confidence: 89%
“…11,12 For example, a 7% rate of grade ՆC dissection with cryoplasty 12 and dissection rates ranging from 1% to 60% with percutaneous angioplasty 13 have been previously described. The low (0.1%) TALON 30-day occlusion and thrombosis rate also compared well with the data previously reported for stents (as high as 4.8% 14 ). Embolism was observed in 0.1% of the lesions treated.…”
Section: Discussionsupporting
confidence: 89%
“…18 Some studies have shown early favorable results, but durability was similar or even worse than for angioplasty. 6,[23][24][25] Three randomized studies [26][27][28] comparing femoropopliteal angioplasty and Palmaz stent placement demonstrated improved technical success (84% for dilation versus 99% for stent 26 ), but the 1-year patency rates were similar for both groups (ϳ60% primary and 80% secondary).…”
Section: Discussionmentioning
confidence: 99%
“…The first phase of SIROCCO demonstrated reduction in intimal hyperplasia in the rapamycin-coated stents, but the difference was not significant. 71 However, strut fractures were noted in both the control arm and the drug-eluting stent arm of SIROCCO, which was one of the first studies to look Figure 3ࡗ Pooled data illustrating the primary patency of various SFA revascularization techniques at 1 to 4 years: angioplasty (subintimal), 30,[93][94][95][96][97][98][99][100][101][102] angioplasty (primary), [8][9][10]14 nitinol stents, [68][69][70][71][72] stents (excluding nitinol), [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] covered stents (Hemobahn), 31,[83][84][85][86][87]…”
Section: Stentingmentioning
confidence: 99%